Pengaruh Budaya Organisasi dan Gaya Kepemimpinan Islami terhadap Kinerja Karyawan PT. Bank Pembangunan Daerah Jawa Timur Tbk. (Bank Jatim Syariah) Kantor Cabang Surabaya, - Nafhatul Ithri, Fina; Cahyono, Hendry (Jurnal Ekonomika dan Bisnis Islam, 2018)
BUS (Bank Umum Syariah) competition is increasingly competitive which requires the company to improving the employees performance. To improving the employees performance by creating a pleasant working environment and also creation of good cooperation between members of the organization. The type of this research is an associative that used a quantitative approach. The sample was taken amount of 50 active employees at Bank Jatim Syariah, Surabaya branch office. The analysis data in this research used classical assumption test, hypothesis test, and path analysis. The result of this research indicate that there is a significant influence between organizational culture to employee performance and Islamic leadership style to employee performance. And then, on the variables of organizational culture and style of Islamic leadership has simultaneous influence on employee performance.